Порівняльна характеристика використання сучасних методів гормональної контрацепції у жінок із надмірною масою тіла - Грідіна, Ірина Борисівна; Гридина, И. Б.; Gridina, I. B. (Запорізький державний медичний університет, 2016)
Збереження репродуктивного здоров’я у жінок із надмірною вагою є актуальною проблемою сьогодення та важливим напрямом сучасної медицини. Велике значення має суб’єктивне оцінювання гормональних контрацептивів жінками з надмірною масою тіла та їхня думка щодо гормональних засобів контрацепції. З метою визначення питань надійності та прийнятності сучасних гормональних контрацептивів у 72 жінок із надмірною масою тіла вивчили переносимість і зручність застосування різних видів гормональної контрацепції. Встановили, що інтравагінальний гормональний контрацептив є найбільш прийнятним як препарат першого вибору для жінок із надмірною масою тіла в порівнянні з оральними і трансдермальними методами гормональної контрацепції. Це свідчить про те, що жінки з надмірною вагою можуть ефективно та безпечно використовувати сучасну гормональну контрацепцію. Але необхідно здійснювати диспансерне спостереження, під час котрого можливі додаткові роз’яснення щодо особливостей застосування гормональної контрацепції в пацієнток із надмірною масою тіла. Сохранение репродуктивного здоровья у женщин с избыточной массой тела – актуальная проблема нашего времени и важное направление современной медицины. Большое значение имеет субъективная оценка гормональных контрацептивов женщинами с избыточной массой тела и их мнение о гормональных средствах контрацепции. С целью определения вопросов надёжности и приемлемости современных гормональных контрацептивов у 72 женщин с избыточной массой тела изучены переносимость и удобство использования разных видов гормональной контрацепции. Установлено, что интравагинальный контрацептив наиболее приемлем в качестве препарата первого выбора для женщин с избыточной массой тела по сравнению с оральными и трансдермальными методами гормональной контрацепции. Это свидетельствует о том, что женщины с избыточной массой тела могут с успехом использовать современные гормональные методы контрацепции. Но необходимо осуществлять диспансерное наблюдение, в ходе которого возможны дополнительные разъяснения об особенностях применения гормональной контрацепции у пациенток с избыточной массой тела. Maintenance of reproductive health of women with excessive weight is the actual problem of nowadays and is an important direction of modern medicine. Aim. To analyze the efficiency and acceptability of oral, іntravaginal and transdermal hormonal contraceptives among women with excessive body mass. Methods and results. The tolerability and ease of use of different types of hormonal contraception have been studied in 72 women with excessive body mass to determine the reliability and acceptability of modern hormonal contraceptives. It has been investigated that the effectiveness of hormonal contraceptives according to our data is 100%, none patient was registered with an unwanted pregnancy. The total subjective evaluation of all hormonal contraceptives use were positive: 78.6% of women with excessive body mass who used oral contraceptives, were satisfied with the chosen contraceptive method, 81,8% – were satisfied with intravaginal method, 59,1% – transdermal contraceptive. Conclusions. It has been found that intravaginal contraceptive is most suitable as the drug of first choice for women with overweight compared with oral and transdermal hormonal methods of contraception. This suggests that women with excessive body mass can successfully use modern methods of hormonal contraception. But it is necessary to carry out clinical supervision, during which further clarification on the use of hormonal contraception in women with excessive body mass is possible.
Сравнительная характеристика использования современных методов гормональной контрацепции у женщин с избыточной массой тела
Comparative description of the use of modern methods of hormonal contraception for women with excessive body mass
Keywords: контрацепція; надмірна вага; тіла маси індекс; контрацепция; избыточный вес; тела массы индекс; Contraception; Overweight; Body Mass Index